Associations of Daily Versus Nondaily Smoking, Tobacco-Related Risk Perception, and Cancer Diagnosis Among Adults in the Population Assessment of Tobacco and Health (PATH) Study. Issue 10 (4th March 2022) - Land, Stephanie R; Baker, Laura; Bachand, Jacqueline; Twesten, Jenny; Kaufman, Annette R; Reyes-Guzman, Carolyn M
Abstract: Introduction: Nondaily smoking has become increasingly common among cigarette smokers. Our objective was to determine whether current daily versus nondaily smoking differed by tobacco-related risk perceptions (TRRPs), demographic factors, and cancer history. Methods: Participants were all adults in Waves 1–3 of the longitudinal cohort Population Assessment of Tobacco and Health Study who were current smokers at Wave 3 ( N = 8307). The primary analysis was weighted logistic regression of daily versus nondaily smoking at Wave 3. TRRP measures were cigarette harm perception, worry that tobacco products will damage one's health, belief that smoking cigarettes causes [lung/bladder/mouth/liver] cancer, and nondaily cigarette harm perception (Likert-type scale). Other measures included demographic factors, other tobacco product use, minor at time of first cigarette, and cancer survivor status (yes/no). Results: Among current smokers, daily versus nondaily smoking was significantly associated with being a minor at time of first cigarette (OR = 1.54, p < .001), TRRPs (OR = 0.83, p < .001; OR = 1.40, p < .001; and OR = 1.17, p = .009 [harm perception, worry, and nondaily cigarette harm perception, respectively]), and interaction between cancer survivor status and belief that smoking causes cancer ( p < .001). TRRPs among current smokers did not differ significantly between cancer survivors and respondents without a cancer history. Conclusions: Respondents with lower harm perception, higher worry, and higher nondaily cigarette harm perception were more likely to be daily versus nondaily smokers. Respondents with higher belief that smoking causes cancer or who were cancer survivors were less likely to be daily (versus nondaily) smokers compared to respondents with low belief and no cancer history. Implications: This study is unique in that it examined associations of smoking cigarettes daily versus nondaily with tobacco-related risk perceptions and cancer survivorship—comparing cancer survivors to those without a cancer history. Given the increasing prevalence of nondaily smoking as compared with daily smoking in the general population, and the prognostic significance of smoking after cancer diagnosis, these findings fill a clinically important gap in the literature and provide a foundation for further research.